2008
DOI: 10.1097/01.nur.0000325383.99717.e5
|View full text |Cite
|
Sign up to set email alerts
|

Think Bar-Code Medication Administration Eliminates Adverse Drug Events? Think Again!

Abstract: I am a clinical nurse specialist (CNS) in an academic medical center that is implementing Bar-Code Medication Administration (BCMA). Does BCMA eliminate errors? How strong is the evidence supporting this expensive technology? What is the impact of BCMA on nursing workflow? B ar-code medication administration is the application of a widely used and reliable commercial technology to prevent medication errors. 1 A unique identifier or bar code placed on each medication is read by an optical scanner. Bar-code medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…34 Also, communication between caregivers, caregiver education, best practice reinforcement, and error reporting policies can help fill in the safety gaps when using the BCMA system. 4039 Ultimately, further patient-safety research is needed to help pinpoint and address errors caused by the BCMA as well as proving the efficiency of the BCMA system in ICU settings.…”
Section: Resultsmentioning
confidence: 99%
“…34 Also, communication between caregivers, caregiver education, best practice reinforcement, and error reporting policies can help fill in the safety gaps when using the BCMA system. 4039 Ultimately, further patient-safety research is needed to help pinpoint and address errors caused by the BCMA as well as proving the efficiency of the BCMA system in ICU settings.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] As a result, many health care professionals think that using bar codes can help to reduce, though not eliminate, medication errors. 13,14 Notably, emergence of the concept of human factors engineering may contribute to more effective management of the introduction and optimal use of bar codes in the medication-use system. 15 The 2009-2010 survey of hospital pharmacy in Canada found that 49% of health care institutions used bar codes (72% of university hospitals and 40% of nonuniversity hospitals).…”
Section: Discussionmentioning
confidence: 99%
“…According to O'Malley ‘bar code medication administration is …[a] unique identifier or bar code placed on each medication which is read by an optical scanner… In addition, the patient is provided a bar code identifier attached to the wristband to ensure correct patient identification' (O'Malley , 269). In the extant empirical literature on bar code medication administration (BCMA), the focus tends to be primarily on safety and/or on how use of these technologies by nurses might affect safety.…”
mentioning
confidence: 99%